Self-propagating High Temperature Synthesis of TiB2 - Turan Ahmet; Bugdayci Mehmet; Yucel Onuralp (High Temperature Materials and Processes, 2015)
Self-propagating high temperature synthesis (SHS) is a very important technique for the synthesis of high technology ceramics, metals and alloys. SHS parameters of TiB2 were carried out in this study. Mg stoichiometry as reductant, process atmosphere and addition of NaCl and MgSO4·7H2O additives were investigated. HCl leaching was applied to SHS products to purify their TiB2 contents. Stoichiometrically 100% Mg addition ratio and Ar atmosphere were determined as the optimum parameters. NaCl addition was also positively affected the specific surface area values. 11.78 m2/g specific surface area value was measured for 5.0% NaCl addition ratio.